Moral Value Analysis in Khaleb Hosseni’s Novel A Thousand Splendid Sun - Grestyana, Nadya Aghe (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2024)
This research purpose is to describe the moral values in A Thousand Splendid Sun novel by Khaleb Hosseni. This research uses a qualitative descriptive method with A thousand Splendid Suns novel by Khaleb Hosseini as the data source. The data procurement procedure is carried out by determining the analysis unit, determining the recording sample or recording the data. In the Thousand Splendid Suns novel, three types of moral values are found in accordance with Nurgyantoro's theory. These types of moral values produce positive and negative attitudes. There are nine positive attitudes, namely; self-confidence, willingness to sacrifice, self-acceptance, gratitude, calm, giving sincerely, obedient to worship, surrender to God, and sincerity. There are also three negative moral attitudes, namely; hatred, self-doubt and doubt of faith. These attitudes were shown by the two main characters in the novel A Thousand Splendid Suns. Novel author described these attitudes directly and indirectly in the form of text and dialogue. The moral values conveyed by this novel can be used as reference material for character learning in schools and society so that the impression of positive character and culture can continue to be preserved in society.